Analisis Manajemen Strategi Peningkatan Pelayanan Pengelolaan PBB Dan BPHTP Pada Dinas Pendapatan Daerah Kota Palembang - Maiza Fikri (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
Strategy management of improving the service quality of property tax management and acquisition cost of land and buildings (BPHTB) at Departement of Revenue Palembang is a research which aims to find out the strategies done by Dispenda in improving the service quality of PBB and BPHTB. This study uses qualitative descriptive research with SWOT analysis and Litmus Test. Based on the research result, it can be concluded that the strategies in improving the service quality of property tax management (PBB)and Acquisition cost of Land and Building (BPHTB) of Departement of Revenue Palembang are Socialize to the tax payer community regarding the awareness of the payment of property tax and acquisition cost of land and building; Improve internal controls to create property tax and acquisition cost of land and building service in accordance with the applicable rules and procedure; and Increase the number of supporting facilities and infrastructures such as counter payments for the tax payers.